2006
DOI: 10.1002/polb.20785
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility and crystallization behavior of PBT/epoxy blends

Abstract: The miscibility and the isothermal crystallization kinetics for PBT/Epoxy blends have been studied by using differential scanning calorimetry, and several kinetic analyses have been used to describe the crystallization process. The Avrami exponents n were obtained for PBT/Epoxy blends. An addition of small amount of epoxy resin (3%) leads to an increase in the number of effective nuclei, thus resulting in an increase in crystallization rate and a stronger trend of instantaneous three‐dimensional growth. For is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…3, values of k and n are obtained from the slope and the intersection of the Avrami plots and the results are also presented in Table 2. It can be seen that the average value of the Avrami exponent n for pure PBT crystallization is about 2.7, which is in good agreement with previously reported data by the other authors [31][32][33][34][35][36] and also indicates the formation of the truncated spherical structure resulting from instantaneous nucleation with diffusion control [37]. The values of n for PBT/silica nanocomposites decrease slightly in comparison with these of pure PBT.…”
Section: Isothermal Crystallization Kinetics and Crystal Morphologysupporting
confidence: 90%
“…3, values of k and n are obtained from the slope and the intersection of the Avrami plots and the results are also presented in Table 2. It can be seen that the average value of the Avrami exponent n for pure PBT crystallization is about 2.7, which is in good agreement with previously reported data by the other authors [31][32][33][34][35][36] and also indicates the formation of the truncated spherical structure resulting from instantaneous nucleation with diffusion control [37]. The values of n for PBT/silica nanocomposites decrease slightly in comparison with these of pure PBT.…”
Section: Isothermal Crystallization Kinetics and Crystal Morphologysupporting
confidence: 90%
“…5 and the parameters obtained are listed in Table 3. It can be seen that pure PBT gives a average n value of about 2.7, which is in accordance with that reported in the literatures [30][31][32][33], indicating the formation of the truncated spherical structure resulting from instantaneous nucleation with diffusion control [34]. With addition of MWCNT, the value of n decreases evidently.…”
Section: Crystallization Kinetics Of Pctssupporting
confidence: 89%
“…An addition of small amount of epoxy resin leads to an increase in the number of effective nuclei, thus resulting in an increase in crystallization rate. Zhang et al 33 have reported that the presence of a small amount of hyperbranched polyurethane acrylate (HUA) remarkably influences the crystallizability of polypropylene. An addition of HUA leads to an increase in the number of effective nuclei, thus resulting in an increase of crystallization rate and a clearer trend of instantaneous three-dimensional growth.…”
Section: Kinetic Analysismentioning
confidence: 99%